Prevention and management of postDural puncture headache (Eurasian Medical Research Periodical, 2022)
A typical side effect of an unintentional Dural puncture is post-Dural puncture headache (PDPH). Female sex, youth, pregnancy, vaginal birth, a low body mass index, and not smoking are risk factors. The risk is also impacted by the method employed, needle size, and needle design. Rapid diagnosis and management are essential for PDPH since it may be incapacitating. A postural headache that gets better with laying down and becomes worse with sitting or standing is a defining feature of PDPH. Conservative therapy including bed rest, hydration, and caffeine are often employed as preventative measures and treatments for this illness; however, neither frequent bed rest nor intensive hydration is backed by strong evidence. The best course of therapy for patients whose conservative measures have failed is an epidural blood patch. A number of alternative preventative and therapeutic options have been proposed. The potential advantages of such therapies should be carefully balanced against the hazards, however, since there isn't enough solid data to justify their usage.